Instruments for assessing social support in social networks and in the self-management and rehabilitation process of persons poststroke : a scoping review protocol - Falk Johansson, Marcus; Taei, Afsaneh ; 0000-0002-1202-7740; McCarthy, Linnea; Gustavsson, Catharina; Tomsone, Signe; Kylén, Maya ; 0000-0003-2887-3674; Elf, Marie (BMJ Open, 2025)
Introduction As care and rehabilitation poststroke are increasingly moving into persons’ home environment, the importance of support from social networks in self-management and rehabilitation has emerged as an important topic for research and practice. While there are instruments used to assess social support and collective efficacy, a clearer scope of the availability and quality of these instruments is needed. This clarification will enable the development of interventions integrating social network perspectives in poststroke rehabilitation. Methods and analysis To assess the availability and quality of instruments assessing social support and collective efficacy, a scoping review will be conducted and reported following the Preferred Reporting Items for Systematic Reviews and Meta-analyses Extension for Scoping Reviews guidelines (PRISMA-ScR). Literature searches conducted between 14 November 2024 and 15 November 2024 in the CINAHL and PubMed/Medline databases resulted in 4631 articles potentially eligible. After removing duplicates, 4121 articles’ titles and abstracts were initially screened. Full-text screening, searches of reference lists and data extraction started in June 2025. Starting August 2025, two reviewers will assess the full texts against the inclusion criteria in Covidence using a coding template. Identified instruments will be appraised following the COSMIN (Consensus-based Standards for the selection of health Measurement INstruments guidelines) and analysed using a narrative descriptive method. Results will be reported in February 2026 according to PRISMA-ScR guidelines. Ethics and dissemination Ethical approval is not required for this scoping review, as it does not involve primary data. However, this review follows established ethical guidelines and best practices, and included studies will be reviewed to ensure that they received ethical approval and included informed consent. Results from the review will be disseminated through an article in a scientific journal, at relevant conferences and surmised to stroke organisations. A policy brief will be developed for health and social care professionals and policy makers.
Keywords: Rehabilitation medicine; Social Support; Stroke